Identify optimal HAP series scores for unresectable HCC patients undergoing TACE plus sorafenib: A Chinese multicenter observational study - Zhu, Yejing; Wang, Enxin; Zhao, Shoujie; Han, Dandan; Zhao, Yan; Chen, Hui; Zhu, Jun; Han, Tenghui; Bai, Yang; Lou, Yanju; Zhang, Yongchao; Yang, Man; et al. (Frontiers in Oncology, 2023)
Abstract Background: Hepatoma arterial-embolisation prognostic (HAP) series scores have been proposed for prognostic prediction in patients with unresectable hepatocellular carcinoma (uHCC) undergoing transarterial chemoembolization (TACE). However, its prognostic value in TACE plus sorafenib (TACE-S) remains unknown; here, we aim to evaluate its prognostic performance in such conditions and identify the best model for this combination therapy. Methods: Between January 2012 and December 2018, consecutive patients with uHCC receiving TACE-S were recruited from fifteen tertiary hospitals in China. Cox regression analyses were used to investigate the prognostic values of baseline factors and every scoring system. Their prognostic and discriminatory performance were evaluated and confirmed in subgroup analyses. Results: A total of 404 patients were enrolled. In the whole cohort, the median follow-up period was 44.2 (IQR: 33.2-60.7) months, the median overall survival (OS) time was 13.2 months, and 336 (83.2%) patients died at the end of the follow-up period. According to multivariate analyses, HAP series scores were independent prognostic indicators of OS. In addition, the C-index, AIC values and time-dependent area under the ROC curve (AUC) indicated that mHAP-III had the best predictive performance. Furthermore, the results remained consistent in most subsets of patients. Conclusion: HAP series scores exhibited good predictive ability in uHCC patients accepting TACE-S, and the mHAP-Ⅲ score was found to be superior to the other HAP series scores in predicting OS. Future high-quality studies should be conducted to confirm our results and help with treatment decision-making.